2018
DOI: 10.1678/rheology.46.37
|View full text |Cite
|
Sign up to set email alerts
|

Flow Temperature of Poly(Lactic Acid) Gel in Solvents with Different Solubility

Abstract: Poly(L-lactid acid) (PLLA) forms complex crystals (ε-crystal) with some solvents including N,N-dimethylformamide (DMF), and can be easily gelled in such solvents. The solvent of these gels can be exchanged to some other solvents which do not form ε-crystal with PLLA. The flow temperatures of PLLA gels after exchanging DMF to various solvents were investigated to clarify the relation between the exchangeability and the solubility of solvents to PLLA. After changing the ε-crystals to α-crystals (crystal form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…PLLA was dissolved in DMF at an elevated temperature, and the solution was successfully formed gels by cooling. [24][25][26][27][28][29][30] The X-ray diffraction pattern of this gel was very similar to the one which had been reported for the PLLA films forming 𝜖-crystals by Marubayashi et al [15] although the peak intensity was weak because the weight fraction of PLLA in the gel was less than 5 wt%. [24] Because the number of solvents inducing PLLA to form 𝜖-crystals is limited, the solvent of the gel was exchange to other solvents by immersing the gel into other solvents which do not form 𝜖-crystals with PLLA, such as water.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…PLLA was dissolved in DMF at an elevated temperature, and the solution was successfully formed gels by cooling. [24][25][26][27][28][29][30] The X-ray diffraction pattern of this gel was very similar to the one which had been reported for the PLLA films forming 𝜖-crystals by Marubayashi et al [15] although the peak intensity was weak because the weight fraction of PLLA in the gel was less than 5 wt%. [24] Because the number of solvents inducing PLLA to form 𝜖-crystals is limited, the solvent of the gel was exchange to other solvents by immersing the gel into other solvents which do not form 𝜖-crystals with PLLA, such as water.…”
Section: Introductionsupporting
confidence: 84%
“…PLLA was dissolved in DMF at an elevated temperature, and the solution was successfully formed gels by cooling. [ 24–30 ] The X‐ray diffraction pattern of this gel was very similar to the one which had been reported for the PLLA films forming ε‐crystals by Marubayashi et al. [ 15 ] although the peak intensity was weak because the weight fraction of PLLA in the gel was less than 5 wt%.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In another work, Matsuda et al described three procedures to elevate the flow temperature of PLLA gel. [ 89–92 ] In the first process, they took PLLA of higher molecular weight and prepared its gel in DMF. The obtained gel was immersed in a DMF solution of PLLA with lower molecular weight and cooled to a temperature of −18°C.…”
Section: Solvent‐induced Gel Formation In Pllamentioning
confidence: 99%
“…From the experiments, it was reported that the flow temperature of the PLLA gel after immersing to 1‐propanol, increased with an increase in the distance of HSPs between PLLA and solvents except for the solvents with low boiling temperature. [ 91 ]…”
Section: Solvent‐induced Gel Formation In Pllamentioning
confidence: 99%